Hypopituitarism as unusual sequelae to central nervous system tuberculosis - S Mageshkumar; Devendra V Patil; J A Philo Aarthy; K Madhavan (Indian Journal of Endocrinology and Metabolism, 2011)
Neurological tuberculosis can very rarely involve the hypophysis cerebri. We report a case of an eighteen year old female who presented with five months duration of generalised apathy, secondary amenorrhea and weight gain. She was on irregular treatment for tuberculosis of the central nervous system for the last five months. Neuroimaging revealed sellar and suprasellar tuberculomas and communicating hydrocephalus requiring emergency decompression. Endocrinological investigation showed hypopituitarism manifesting as pituitary hypothyroidism, hypocortisolism, hypogonadotropic hypogonadism, and hyperprolactinemia. Restarting anti-tuberculosis treatment, hormone replacement therapy, and a ventriculo-peritoneal shunt surgery led to remarkable improvement in the general condition of the patient.